Results of multiple myeloma treatment with bortezomib - T. I. Pospelova; N. V. Skvortzova; I. N. Nechunaeva (Онкогематология)
Bortezomib efficacy in I, II and subsequent therapy lines was studied at 51 multiple myeloma (MM) patients in Novosibirsk Hematological Center. The median of age was 66 years (39—87); patients have received from 4 to 12 therapy courses, totally — 363 courses. Total efficacy of the I line therapy was 80%. Complete remission has been achieved in 60% of patients. Efficacy of Bortezomib monotherapy and in combination with glucocorticoids in case of progression and refractory MM was 75,7%. Bortezomib was effective even at repeated administration to patients had receied it or other components of combined regimes earlier (total response — 46,2%). Bortezomib side effects were predicted and managed; most significant of them are gastrointestinal, hematologic, asthenia and peripheral neuropathia. Thus, bortezomib is highly effective drug, important in MM therapy as I and subsequent therapy line and result in significantly increase of overall survival.